Taliban Strategies and Gains in Post-American Reality in Afghanistan - Rahaman, Md Shafiqur; Rahman, Md Anisur (Journal of Al-Tamaddun, 2025)
This paper aims to explore the re-establishment of the Taliban regime in Afghanistan in the frame of the emerging bipolar world order, addressing the post-American realism. We address two significant perspectives: First, the Taliban’s re-emergence as a dominant political and military force in Afghanistan, despite two decades of U.S. military intervention, infrastructural devastation, and extensive state-building efforts, reflects a combination of organizational resilience, strategic adaptability, and the mobilization of deeply rooted socio-religious narratives. The Taliban capitalized on widespread disillusionment with the U.S.-backed Afghan government, which was often perceived as corrupt, externally dependent, and disconnected from rural constituencies. Their ability to sustain a decentralized yet cohesive insurgency, embed themselves within local communities, and frame their struggle as both a nationalist resistance and a religious obligation allowed them to gradually undermine the legitimacy of the foreign-supported order and reclaim political relevance. Second, following the withdrawal of U.S. forces in 2021, the Taliban successfully positioned themselves as the central political authority in Afghanistan, despite the non-recognition of their regime by the United States and its Western allies. Their consolidation of power was facilitated by their military dominance, the collapse of the U.S.-backed Afghan government, and their ability to negotiate local allegiances. Moreover, the Taliban leveraged Afghanistan’s political vacuum to establish a de facto government, asserting internal legitimacy and seeking to navigate the complexities of international isolation through pragmatic diplomatic engagements, particularly with China and regional actors. This study employed a qualitative content analysis approach, utilizing semi-structured, in-depth face-to-face interviews as the primary method of data collection. Interviews were conducted with Afghan graduate and postgraduate students residing in Russia, as well as with four local residents from various cities in Afghanistan, including Kabul, Kandahar, Mazar-i-Sharif and Herat. For the interviews with local residents, an online platform was utilized to facilitate communication. Both direct and indirect questions were posed to the participants during the interviews to explore and substantiate the research hypotheses. The insights derived from these interviews provided a nuanced understanding of contemporary realities, particularly in relation to the political dynamics of the Taliban and the broader context of Afghanistan. In addition to primary data, secondary sources such as internet-based materials and media reports were analyzed to further examine the post-American reality in Afghanistan. Furthermore, theoretical perspectives from contemporary scholars addressing the post-American world order were incorporated to support and legitimize the study’s arguments.